2019
DOI: 10.3168/jds.2018-16144
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for noise reduction and standardization of milk mid-infrared spectra from dairy cattle

Abstract: The use of Fourier-transform mid-infrared (FTIR) spectroscopy is of interest to the dairy industry worldwide for predicting milk composition and other novel traits that are difficult or expensive to measure directly. Although there are many valuable applications for FTIR spectra, noise from differences in spectral responses between instruments is problematic because it reduces prediction accuracy if ignored. The purpose of this study was to develop strategies to reduce the impact of noise and to compare method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
(44 reference statements)
3
14
0
Order By: Relevance
“…Many studies are based on spectra from a single instrument, and are therefore not required to account for the different variance-covariance structures of measurements from different instruments. In a study of spectra from 66 instruments, Grelet et al [42] showed considerable variability in the spectral responses of the instruments, while we have also observed that the distribution of MD values can be heterogeneous across instruments [43]. These results highlight the need to apply MD thresholds within instrument for the purpose of outlier removal.…”
Section: Outlier Removal and Removal Of Low Signal-to-noise Regions Osupporting
confidence: 58%
See 3 more Smart Citations
“…Many studies are based on spectra from a single instrument, and are therefore not required to account for the different variance-covariance structures of measurements from different instruments. In a study of spectra from 66 instruments, Grelet et al [42] showed considerable variability in the spectral responses of the instruments, while we have also observed that the distribution of MD values can be heterogeneous across instruments [43]. These results highlight the need to apply MD thresholds within instrument for the purpose of outlier removal.…”
Section: Outlier Removal and Removal Of Low Signal-to-noise Regions Osupporting
confidence: 58%
“…More generally, Bittante and Cecchinato [44] showed that the transmittance of individual spectra wavenumbers had moderate to high heritability across most of the mid-infrared region and highlighted that absorbance peaks for non-water milk components were present in low signal-to-noise ratio regions and should be considered for investigation. The findings of these studies indicate that a prudent approach to removal of wavenumbers in low signal-to-noise ratio regions should be taken, retaining spectra from all regions in applications where the wavenumbers are considered independently, but removing them in applications where wavenumbers are considered in a multivariate manner [43].…”
Section: Outlier Removal and Removal Of Low Signal-to-noise Regions Omentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these proprietary predictions change over time, even within a manufacturer. Standardization efforts can reduce background noise and prediction errors and are sensitive to milk composition shifts (Tiplady et al, 2019). These differences may not be as evident to producers viewing results from a single DHI laboratory, but if research is based on separate platforms, there may be limitations to on-farm application based on the equipment used by the DHI or in-line system.…”
Section: On-farm Integration Of Herd-health Diagnostics Challenges and Opportunitiesmentioning
confidence: 99%